Novel mutations of STXBP2 and LYST associated with adult haemophagocytic lymphohistiocytosis with Epstein-Barr virus infection: a case report - Lingshuang Sheng; Wei Zhang; Jia Gu; Kefeng Shen; Hui Luo; Yang Yang (BMC, 2019)
Abstract Background Haemophagocytic lymphohistiocytosis is a life-threatening disease resulting from primary or secondary hyper-inflammatory disorders. The typical symptoms include persistent fever, splenomegaly, cytopenia and significant elevation of serum ferritin. Case presentation We report a 30-year-old Chinese female patient who was diagnosed with chronic active Epstein-Barr virus infection more than 9 months prior and has since been presenting with cutaneous lymphoproliferative disorders mimicking hydroa vacciniforme and subsequent haemophagocytic lymphohistiocytosis. Exome sequencing suggested novel digenic heterozygous STXBP2 (c.592A > C, p.Thr198Pro) and LYST (c.830A > T, p.His277Leu) mutations. Conclusions This is the first case report in which adult HLH was associated with novel digenic mutations of STXBP2 and LYST combined with Epstein-Barr virus infection. It could also be the first polygenic model report, given that the pathogenicity of other mutated genes still remains unclear. We additionally conducted an in-depth, two-generation pedigree analysis to further illustrate the mode of inheritance in this case.